2014
DOI: 10.1002/jid.3020
|View full text |Cite
|
Sign up to set email alerts
|

Welfare Impacts of Microcredit Programmes: An Empirical Investigation in the State‐Designated Poor Counties of Shaanxi, China

Abstract: This paper evaluates the welfare impacts of microcredit programmes and the activities of non-governmental organization microfinance service providers in state-designated poor counties of Shaanxi, China. Study results suggest positive impacts on microcredit programme participants with respect to increased income (by 4.07 per cent), general expenditures (6.45 per cent) and savings (3.13 per cent). Top income quartile participants experience more benefits, and women gain greater access to decision-making. These f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
13
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 24 publications
4
13
1
Order By: Relevance
“…The results also showed that the access to microcredit positively and significantly (P < 0.01) affected the control over savings by rural women ( Table 7). The results indicate that the rural women respondents who obtained microcredit have more control over savings, which is consistent with the findings of Li et al (2011) and Rahman et al (2015). The probability of controlling their savings (CSAV) was higher for borrowers (0.78) than non-borrowers (0.48) (Table 8).…”
Section: Impact Of Microcredit On Control Over Financial Assets/resousupporting
confidence: 86%
“…The results also showed that the access to microcredit positively and significantly (P < 0.01) affected the control over savings by rural women ( Table 7). The results indicate that the rural women respondents who obtained microcredit have more control over savings, which is consistent with the findings of Li et al (2011) and Rahman et al (2015). The probability of controlling their savings (CSAV) was higher for borrowers (0.78) than non-borrowers (0.48) (Table 8).…”
Section: Impact Of Microcredit On Control Over Financial Assets/resousupporting
confidence: 86%
“…They are nevertheless consistent with the studies that found the unfavourable socio-economic effects of MFI microcredit (e.g. Adams & Von Pischke, 1992;Morduch, 1998;Coleman, 1999;Garikipati, 2008;Liv, 2013;Renzenbrink, 2013;Song, 2013;Ovesen & Trankell, 2014;Bylander, 2015;Seng, 2017a), revealing the MFIs' drift away from their original social mission to fight poverty, in Cambodia in particular. These results confirm Seng's (2017a) important findings that microcredit 'has at best no effect on household welfare, and may have an adverse effect', demonstrating cracks in its povertyalleviating promise.…”
Section: Microcredit's Poverty-reducing Promise 629supporting
confidence: 90%
“…Microcredit's failure to break the women's poverty cycle is caused by the fact that women generally invest in low profit business and may repay loans by borrowing from other financial sources, leading to a heavy debt burden (IFAD, 2011;Seng, 2017a). These findings support an argument by Adams and Von Pischke (1992) that microfinance loans do little to lift poverty-stricken households out of the poverty trap nor can they enhance the vulnerable households but very likely worsen household poverty. Recent studies on the development of microcredit in Cambodia demonstrate that formal and informal microloans are very likely used together by poor borrowers (e.g.…”
Section: Literature Reviewmentioning
confidence: 76%
See 2 more Smart Citations